Application of a dealginated seaweed derivative for the simultaneous metal ions removal from real and synthetic effluents. (October 2020) - Costa, Camila Stéfanne Dias; Bertagnolli, Caroline; Boos, Anne; da Silva, Meuris Gurgel Carlos; Vieira, Melissa Gurgel Adeodato
Graphical abstract: Highlights: Toxic metals were successfully removed from simulated and real effluents by RES. Temperature increase had inductive effect on metals removal, especially for Cr. Unknown affinity for Al and Pb was found for real waters, with up to 80 % removal. Involvement of carboxylic and hydroxyl groups was revealed by characterizations. Total binding strength ( ξ ) was: Cr > Al > Ni ≈ Pb > Zn > Mg > Ca > H > K > Na. Abstract: In this study, the alginate extraction residue (RES) from Sargassum filipendula was employed as biosorbent for the simultaneous removal of Cr 3+, Ni 2+ and Zn 2+ from ternary synthetic solutions and for the decontamination of industrial (leather industry) and urban real effluents that were collected from different areas of Strasbourg (France). For this purpose, biosorption experiments in batch mode, multimetals equilibrium isotherms fitting and biosorbent characterization were carried out. In synthetic effluents, RES exhibited a greater affinity for Cr 3+ ions, while a still unknown affinity for Al 3+ and Pb 2+ was verified for real conditions, reaching up to 80 % removal in some cases. At equilibrium, the higher sorption capacities were found at 50 °C as 0.864, 0.302 and 0.347 mmol/g for Cr 3+, Zn 2+ and Ni 2+, respectively. Regarding the equilibrium models fitting, just the Extended Langmuir equation was able to describe the experimental data, showing an increase in qmax as the temperature rose, besides a decay in KL, 1, KL, 2 and KL, 3 at the higher temperatures that indicates a weakening of adsorbent-adsorbate interactions. The characterization analyzes revealed a complex biosorption with a depth participation of carboxylic and hydroxyl groups was revealed by the characterization analyses, whereas the ion exchange mechanism played a really important role. The cation exchange capacity of RES was quantified as 34.12 mg/gRES with main exchangeable position of Ca 2+ and Na + ions. Based on these results, RES could be used as a novel and efficient biosorbent for toxic metals removal even from quite diluted real effluents, contributing to its valorization.